Life Cycle Approach to Shopping Mall Redevelopment: A Model for Service Life Design - Jasmina Tamburić; Vladan Nikolić; Dragoslav Stojić; Olivera Nikolić (Applied Sciences)
This study investigates the enhancement of condition and the extension of service life in architectural structures of shopping malls through the application of a hybrid methodological framework that integrates Life Cycle Assessment (LCA) and Service Life Planning (SLP). Thisresearch identifies key parameters related to physical performance, sustainability indicators, and functional characteristics of architectural systems that are subject to deterioration and shifting market conditions during the operational phase. The methodology encompasses a theoretical synthesis of LCA/SLP principles and advances in modeling for both the integrated design of new facilities and the monitoring and renewal of existing ones—from data collection and early-stage planning, through construction, use, and maintenance, to end-of-life phases. A second component of the model focuses on quantitative assessment and condition forecasting, based on Markov chain modeling, applied to the case study of the “Deva 1” shopping mall in Serbia. The results demonstrate the model’s ability to correlate physical condition indices with predictive service life scenarios.This study further contributes by integrating time-dependent impact categories, usage profiles, and planning parameters into a unified evaluation matrix, which can be applied to the development and improvement of systems aimed at enhancing the structural, functional, esthetic, and indirectly economic value of shopping mall buildings throughout their entire life cycle—from an architectural perspective.